2009
DOI: 10.1348/014466608x387098
|View full text |Cite
|
Sign up to set email alerts
|

Does mood really influence comparative optimism? Tracking an elusive effect

Abstract: Methodological limitations call into question prior evidence that positive moods are associated with greater comparative optimism. Experiments 1-4 tested if mood affects comparative optimism using a mood manipulation that minimized experimenter demand. While the procedure was successful in inducing mood, we found no evidence for a mood effect on comparative optimism. The absence of a mood effect was not due to participants correcting their judgments in response to a presumed mood bias (Experiments 2, 3 and 4) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
0
8
0
2
Order By: Relevance
“…Finally, evidence suggests that negative mood and prior experience with a negative event can decrease both unrealistic absolute optimism and unrealistic comparative optimism, primarily because both appears to affect personal risk estimates rather than risk estimates for others (Helweg-Larsen & Shepperd, 2001). However, not all studies have replicated this mood effect (Drace et al, 2009). …”
Section: Questions That Remainmentioning
confidence: 99%
“…Finally, evidence suggests that negative mood and prior experience with a negative event can decrease both unrealistic absolute optimism and unrealistic comparative optimism, primarily because both appears to affect personal risk estimates rather than risk estimates for others (Helweg-Larsen & Shepperd, 2001). However, not all studies have replicated this mood effect (Drace et al, 2009). …”
Section: Questions That Remainmentioning
confidence: 99%
“…Participants were shown each of the pictures for their condition for 15 seconds, with a gap of 5 seconds between pictures, during which time the screen was black. Participants in the neutral and strong negative mood conditions were exposed to the standard procedure (e.g., Drace et al, 2009Drace et al, , 2010 asking them to look at the pictures and try to vividly imagine themselves as witness-1 The following pictures were used for the mood inductions. Neutral mood: 2190, 2385, 2514, 2516, 2749, 2840, 2890, 5510, 5531, 5534, 7004, 7006, 7009, 7010, 7020, 7050, 7160, 7170, 7175, 7185, 7187, 7207, 7211, 7217, 7233, 7235.…”
Section: Methodsmentioning
confidence: 99%
“…Participants in the moderate negative mood condition received the same instructions but were exposed to shorter inductions during which they watched only 8 pictures, which were randomly selected from a set of 24 pictures used in the strong condition. Prior work showed that sustained presentation of a series of pictures of similar valence produces emotional reactions that are sensitized across the temporal intervals (Bradley, Cuthbert, & Lang, 1996;Smith, Bradley, & Lang, 2005) and that it could be an efficient method to manipulate the intensity of negative mood (Drace et al, 2009). After the mood induction, participants were first asked to fill in the BMIS and once they finished they were instructed to position themselves in front of a response box on the same table.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations